Respuesta :

Answer:

x = 5/13

Step-by-step explanation:

Given [tex]x \frac{4}{x} - \frac{6}{4x} = \frac{1}{10}[/tex]:

First, cancel out the fraction of the first term:

[tex]x\frac{4}{x}[/tex] = 4

This leaves you with:

[tex]4 - \frac{6}{4x} = \frac{1}{10}[/tex]

Cancel out the common factor (of 2) from the second term, -6/4x:

[tex]4 - \frac{3}{2x} = \frac{1}{10}[/tex]

Next, we need to find the LCM of 2x and 10, which is 10x:

Multiply the terms by the LCM = 10x:

[tex](10x) 4 - \frac{3}{2x} (10x) = \frac{1}{10} (10x)[/tex]

Simplify:

40x - 15 = x

Subtract x from both sides:

40x - x - 15 = x - x

39x - 15 = 0

Add 15 to both sides:

39x - 15 + 15 = 15

39x = 15

Divide both sides by 39 to solve for x:

39x/39 = 15/39

x = 5/13

Please mark my answers as the Brainliest, if you find this helpful :)

Answer:

[tex]{ \rm{x \frac{4}{x} - \frac{6}{4x} = \frac{1}{10} }} \\ \\ { \rm{4 - \frac{6}{4x} = \frac{1}{10} }}[/tex]

• simplify further:

[tex]{ \rm{ \frac{6}{4x} = 4 - \frac{1}{10} }} \\ \\ { \rm{ \frac{6}{4x} = \frac{39}{10} }} \\ \\ { \rm{4x \times 39 = 6 \times 10}} \\ \\ { \rm{156x = 60}} \\ \\ { \boxed{ \rm{ \: \: x = \frac{5}{13} \: \: }}}[/tex]

ACCESS MORE